Potret Perilaku Konsumsi Mahasiswa-Santri Pondok Pesantren Mahasiswa UII dan Pondok Pesantren Mahasiswa Pandanaran Komplek IV Yogyakarta - Muhammad Qamaruddin (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2020)
In order to meet the needs of life, humans are required to carry out consumption activities by using and utilizing goods and services. The purpose of this study was to conduct an in-depth analysis related to the consumption behavior of the Santri Islamic Boarding School Students and Islamic Boarding Schools in Sunan Pandanaran Campus IV Yogyakarta. This research is qualitative, the method of collecting data is by doing some questionnaires, observations, interviews, and documentation. The results of the data analysis are continued in the descriptive analysis. The results of this study showed that the consumption behavior of students in both Islamic Boarding in-line with the principles of Islamic teaching.